2017
DOI: 10.2215/cjn.08460816
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Multidimensional Measure of Dialysis Adequacy—Moving beyond Small Solute Kinetics

Abstract: Urea removal has become a key measure of the intensity of dialysis treatment for kidney failure. Small solute removal, exemplified by Kt/V has been broadly applied as a means to quantify the dose of thrice weekly hemodialysis. Yet, the reliance on small solute clearances alone as a measure of dialysis adequacy fails fully to quantify the intended clinical effects of dialysis therapy. This review aims to () understand the strengths and limitations of small solute kinetics as a surrogate marker of dialysis dose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 94 publications
0
68
0
4
Order By: Relevance
“…A better understanding of patient‐reported outcomes may allow kidney care practitioners to facilitate a patient‐centered approach to dialysis modality selection . Ongoing patient involvement in research may help set research priorities for the future and this may facilitate more effective communication between health care professionals and patients in education surrounding dialysis treatment options.…”
Section: Our Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better understanding of patient‐reported outcomes may allow kidney care practitioners to facilitate a patient‐centered approach to dialysis modality selection . Ongoing patient involvement in research may help set research priorities for the future and this may facilitate more effective communication between health care professionals and patients in education surrounding dialysis treatment options.…”
Section: Our Opinionmentioning
confidence: 99%
“…A better understanding of patient-reported outcomes may allow kidney care practitioners to facilitate a patient-centered approach to dialysis modality selection. 97…”
Section: Quality Of Life and Patient-reported Outcomesmentioning
confidence: 99%
“…Interestingly, a Chinese study found an association between sp Kt / V and LVMI in HD patients . These measures are easily performed, although their overall usefulness as surrogate markers for cardiovascular risk need to be more accurately quantified to dictate guidance regarding the frequency of measurement and appropriate targets …”
Section: The Elephants In the Roommentioning
confidence: 99%
“…Classically measures of dialysis adequacy since have been based on small solute clearance using urea and creatinine and are defined as the minimum urea clearance and nutritional intake that prevent adverse outcomes [1]. …”
Section: Introductionmentioning
confidence: 99%